Identifying Energy Savings Opportunities for a Multi-use Venue Building (Future Cities and Environment, 2018)
Multi-use venue buildings are an extreme example of buildings with ffexible use. Such buildings have high occupant diversity factors and inconsistent occupant-building interaction leading to highly changeable demands of the building services. Intensive monitoring of a case study multi-use venue building was carried out in order to analyse its energy performance and identify energy saving opportunities. Results are presented from three distinct uses of the building, with each analysed as a separate case study. The analysis focused on exploring relationships between variables for each event; identifying multiple energy savings opportunities. Poor building management system (BMS) scheduling led to 49% of total gas use across all three events being estimated as waste, whereas inappropriate set points accounted for 7%. Event organiser behaviour led to 6% of total electricity across all three events estimated as waste, whereas inffexible controls accounted for 2%. Based on these results, venue building managers may ffnd that prior knowledge of building activity and more accurate occupancy hours could yield signiffcant energy savings through proactive energy management.